ANALYSIS OF CHANGES IN PUBLIC SERVICES POPULATION ADMINISTRATION FOR SAMIN BELIEFS IN PATI - Wahyuni, Husnia Hilmi; Gravionika, Elsa; Afda’u, Faisal (UNTAG Law Review, 2024)
Believers are a group of people who experience discrimination in the administrative system in relation to the religion column in the e-KTP. In general, when viewed from the population administration, the location of adherents of beliefs, adherents of ancestral religions and the implementation of rituals in adat makes it difficult for them during state administration in personal documents such as electronic identity cards (KTP), family cards (KK), marriage certificates. , and birth certificates. Based on the article of the Population Administration Lawwhich explains that religion in the religion column on the family card (KK) and electronic identity card (KTP) for adherents of faith is not filled in fundamentally, this is because the sect has not been recognized as well as other religions. another, so that in the electronic identity card (KTP) there is no record that someone is a believer. Meanwhile, the Population Administration Law is factually or at least potentially detrimental to constitutional rights. This is where discrimination arises against people who do not yet have an awareness of human rights. Cases of discrimination against adherents of certain religions are even carried out by bureaucracy, although the 1945 Constitution has stated to free people to practice their respective religions and beliefs.